FRI0275 Change in CXCL4 Levels May Predict Treatment Response in Systemic Sclerosis-Related Interstitial Lung Disease (SSC-ILD). (15th July 2016) - Volkmann, E.; Tashkin, D.; Elashoff, R.; Tseng, C.-H.; Khanna, D.; Mayes, M.; Charles, J.; Clements, P.; Roth, M.; Furst, D.; Assassi, S.; ,
Abstract : Background: Baseline circulatory levels of the chemokine CXCL4 have been associated with both extent and progression of SSc-ILD 1 . No studies have examined whether changes in CXCL4 levels may predict progression of SSc-ILD. Objectives: To determine whether CXCL4 levels change in response to treatment for SSc-ILD and to explore whether these changes predict future progression of SSc-ILD. Methods: All SSc-ILD patients enrolled in the Scleroderma Lung Study (SLS) II (Comparing 2 years of mycophenolate [MMF] versus 1 year of cyclophosphamide [CYC] followed by 1 year of placebo) were included. CXCL4 levels were measured at baseline, 12 and 24 months using validated, commercially available ELISA kits (Human CXCL4/PF4 Quantikine Kit - R&D Systems). CXCL4 levels were log-transformed. Spearman's correlations were performed to examine the relationship between the change in CXCL4 levels from baseline to 12 months and the change in the FVC from baseline to 18, 21, and 24 months. A mixed effects model was created to determine whether the change in CXCL4 from baseline to 12 months predicted the course of the FVC from 12 to 24 months, while controlling for treatment arm and baseline ILD severity. A T-test was used to compare the change in CXCL4 from baseline to 12 months between patients who experienced a clinically meaningful improvement in FVC at 24 months (defined as a ≥5% increase in FVC from baseline) and those who did not. Results: Of the 142 patients in SLS II, 136 had CXCL4 levels measurements performed. The mean FVC% predicted for this cohort was 66.5 and the mean disease duration was 2.5 years. CXCL4 levels decreased significantly in both treatment arms at 12 months (Mean difference: CYC -0.71 [1.4], P <0.001; MMF -0.32 [0.86], P =0.006) and at 24 months (Mean difference: CYC -0.53 [1.3], P <0.001; MMF -0.43 [1.1], P =0.01). There was no significant difference in the change in CXCL4 levels between treatment groups at 12 ( P =0.12) or 24 months ( P =0.38) (Figure 1 ). There was a trend for a significant relationship between the change in CXCL4 level at 12 months and the change in the FVC from baseline to 18 months (r= -0.2; p =0.06), 21 months (r= -0.21; p =0.06), and 24 months (r=-0.18; p =0.08). In the mixed effects model, the change in CXCL4 level at 12 months significantly predicted the course of the FVC from 12 to 24 months (Estimate -1.2; Std Err 0.6; p =0.04). Patients with a ≥5% increase in FVC at 24 months had a greater decrease in CXCL4 levels compared with patients with a <5% increase in FVC at 24 months (-0.83 [1.46] vs. -0.24 [0.94]; P =0.03). Conclusions: Treatment with immunosuppression led to significant decreases in CXCL4 levels in patients with SSc-ILD. Patients who experienced the greatest decrease in CXCL4 from baseline to 12 months had improved course of FVC from 12 to 24 months, suggesting that short-term change in CXCL4 may be a potential biomarker for predicting long-term treatment response in SSc-ILD. References: van Bon, et al. NEJM 2014;370:433–43. Disclosure of Interest: None declared